The influence of propionibacteria on in vivo rumen fermentation characteristics and in vitro lactic acid clearance rate in fistulated steers fed moderately high concentrate diets - Gifford, Ryan J., author; Engle, Terry E., advisor; Wagner, John J., committee member; Torres-Henderson, Camille, committee member (Colorado State University. Libraries, 2022)
The objective of this experiment was to determine the impact of a direct fed microbial (DFM) supplementation on rumen fermentation characteristics and in vitro lactic acid clearance. Fistulated steers (n = 6) were sorted into two groups of three steers, randomly assigned to one of two treatments, and fed a moderately high concentrate diet (14.9% CP, 1.17 Mcal/kg NEg, and 28.3% NDF) for 21 d prior to beginning the experiment. Treatments consisted of: 1) Control (No DFM; carrier only) or 2) DFM (0.225g∙animal-1∙day-1 of 4.45x 1010 CFU/g of Propionibacteria acidipropionici - CP88). Treatments were administered daily, directly into the rumen via the cannula as a single bolus dose at the time of feeding. Immediately after treatment administration, the rumen contents were thoroughly mixed by hand. Two hours post feeding, rumen pH was determined, and rumen contents were sampled and analyzed for short chain fatty acids (SCFA), daily. On d 7 and 14, rumen fluid was collected from all steers and subjected to an in vitro lactic acid clearance challenge. Lactic acid and SCFA concentrations were determined at 0, 3, 6 and 9 h post-incubation. After d 14, all cattle received the basal diet for 21 d. On d 22, treatment crossover was implemented, and the experiment repeated. Data were analyzed by a mixed effects completely randomized block design (Proc Mixed, SAS Inst. Carey, NC). There were no treatment x block, treatment x time, or treatment x block x time interactions for any in vivo or in vitro rumen variables measured. Propionic acid concentrations were greater (P < 0.05) and total SCFA tended (P < 0.06) to be greater in rumen fluid from steers receiving DFM compared to controls. Other in vivo rumen fermentation characteristics were similar. D- and total lactic acid concentrations but not L+ lactic acid concentrations were lesser (P < 0.05) at 3 h post incubation in vitro, for steers receiving DFM. D-, L+, and total lactic acids concentrations were similar between control and DFM treatments at 0, 6, and 9 h post incubation. In vitro molar proportions of propionic acid and total SCFA concentrations were greater (P < 0.05) and acetic acid molar proportions were lesser (P < 0.05) in steers receiving DFM. Collectively, under the conditions of this experiment, these data indicate that the DFM test article (P. acidipropionici - CP88) used in this experiment alters rumen fermentation characteristics in vivo, and in vitro, and lactic acid utilization in vitro.
Keywords: fermentation; short chain fatty acids; lactic acid; direct fed microbial